OPTICAL CHARACTER RECOGNITION MENGGUNAKAN ALGORITMA TEMPLATE MATCHING CORRELATION - Suryo Hartanto; Aris Sugiharto; Sukmawati Nur Endah (Journal of Informatics and Technology, 2012)
OCR (Optical Character Recognition) is an effective solution to the process of converting printed documents into digital documents. The problems that arise in the process of computer letters recognition is how a recognition techniques to identify different types of characters with different sizes and shapes. Recognition method used in this final project is the template matching correlation method. Prior to the recognition process, the input image with a format *.bmp or *.jpg processed first at the preprocessing process, which includes the binerisasi, segmentation, and normalization of images. Average recognition success rate of 92,90% is generated by this system. The final results showed that the use of the template matching correlation method is effective enough to build an OCR system with good accuracy.